Risk Factors Associated with the Participation of Women of Reproductive Age (WRA) in Early Detection of Cervical Cancer Using Visual Inspection with Acetic Acid (VIA) Method in Maros Regency, Indonesia - Tria Dwi Astuti; Nur Nasry Noor; Ida Leida Maria; Wahiduddin; Thamrin, Yahya; Tawali, Suryani (National Journal of Community Medicine, 2023)
Introduction: This study aims to determine the relationship between the participation of Women of Reproductive Age (WRA) in early detection of cervical cancer using the Visual Inspection with Acetic Acid (VIA) method. Methods: This study used an analytic observational research design with a case control study design with a total sample size of 180 consisting of 90 cases and 90 controls selected by systematic random sampling method. Data analysis was carried out using STATA version 14 program. Results: There is a significant relationship with the participation of WRA in early detection of cervical cancer using VIA method, namely the level of education (OR = 2.42; CI 95%: 1.26 - 4.66; p = 0.041), accessibility of public health center (OR = 2.10; CI 95%: 1.07 - 4.13; p=0.019), husband’s support (OR= 8.80 (95% CI: 4.18 – 18.81; p= 0.000), the role of public health center employees (OR= 2.87; CI 95%: 5.76; p=0.001) and information media exposure (OR= 2.72; CI 95%: 1.42 - 5.20; p=0.001). The factors that were not significantly related was work (OR= 1.35; 95% CI: 0.64 – 2.81; p = 0.389). Conclusion: It is necessary to improve the quality of counselling thoroughly by health workers.